BENCHMARKING OF TWO SYSTEMS FOR TRANSMISSION OF MOTION FOR A DOUBLE ACTION STIRLING ENGINE - e Paula, R. B.; Antunes, P. D.; Souza, P. O.; Leme, M. M. V. (Revista de Engenharia Térmica, 2013)
In a four-piston Stirling engine, Siemens configuration, the displacement of the pistons is governed by the motion transmission element, which converts the reciprocating motion of pistons into rotary motion. This study aimed to evaluate the influence of the geometry of the transmission element in the mechanical efficiency of a Stirling engine. Analyses were performed using a mathematical computer simulation that uses the geometric and operating data of the engine to calculate the mechanical power and efficiency through a first order thermodynamic mathematical model, also known as the Schmidt model. First, an analysis was performed to evaluate the mechanical efficiency of the transmission element with a sinusoidal curve surface. Later, it was implemented in the transmission mechanism a segment based straight plans surface, and then the same analysis was performed with this new transmission element. The results showed that using the transmission element with segment based straight plans the engine showed a significant increase in efficiency. Moreover, one can observe an increase in the vibration of the system, making it necessary to develop an appropriate system for balancing.